CONSUMER INFORMATION SYSTEM IN WEB-BASED COOPERATIVES: CASE STUDY OF DIRA JAYA SINAR RESKI COOPERATIVE - Fathin, Fathin Kartika; Saharuddin, Saharuddin; Fathahillah, Fathahillah (Journal of Electrical Engineering and Informatics, 2024)
This study aims to determine the results of the development of consumer information systems at the Dira Jaya Sinar Reski cooperative as well as find out user responses to the system to be developed. This research uses the type of R&D (Research and development) research and prototype development model that uses data collection techniques such as interviews, observations, and questionnaires. Based on the results of the research, a Web-Based Consumer Information System was developed at the Dira Jaya Sinar Reski Cooperative which has been tested using ISO 25010 testing using 8 aspects of testing that have been validated by content experts. The final result of the overall assessment is that the Consumer Information System at the Web-Based Dira Jaya Sinar Reski Cooperative was declared valid by the validator lecturers, and declared effective based on functional suitability aspects, and declared practical based on user responses that have been tested from the usability aspect.